2021
DOI: 10.1016/j.omtn.2021.07.022
|View full text |Cite
|
Sign up to set email alerts
|

ERα determines the chemo-resistant function of mutant p53 involving the switch between lincRNA-p21 and DDB2 expressions

Abstract: Mutant p53 (mutp53) commonly loses its DNA binding affinity to p53 response elements (p53REs) and fails to induce apoptosis fully. However, the p53 mutation does not predict chemoresistance in all subtypes of breast cancers, and the critical determinants remain to be identified. In this study, mutp53 was found to mediate chemotherapy-induced long intergenic noncoding RNA-p21 (lincRNA-p21) expression by targeting the G-quadruplex structure rather than the p53RE on its promoter to promote chemosensitivity. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…However, DDB2 is reported to have dual functions in cancer, sometimes with tumor suppressive properties and sometimes functioning as an oncogene ( 34 ). In cancer cells, DDB2 may also promote the repair of cancer DNA lesions induced by radiation or chemotherapy leading to chemo/radioresistance ( 34 36 ) ( 11 ). The transcription factor p53 plays critical roles in the suppression of tumor development, and MDM2 is the primary negative regulatory factor of p53 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, DDB2 is reported to have dual functions in cancer, sometimes with tumor suppressive properties and sometimes functioning as an oncogene ( 34 ). In cancer cells, DDB2 may also promote the repair of cancer DNA lesions induced by radiation or chemotherapy leading to chemo/radioresistance ( 34 36 ) ( 11 ). The transcription factor p53 plays critical roles in the suppression of tumor development, and MDM2 is the primary negative regulatory factor of p53 ( 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…LincRNA-p21 , also called p53 pathway corepressor 1 protein tumor ( TRP53COR1 ), is associated with VDR signaling [ 80 ]. It was shown that its expression was induced by chemotherapy and mediated by a mutated p53 form that targeted the G quadruplex structure rather than the p53 response elements in its promoter [ 91 ]. It was shown that lincRNA-p21 was upregulated in 4T1 breast tumor-associated macrophages (TAMs) [ 92 ].…”
Section: Long Noncoding Rnas and Vitamin D Signaling In Breast Cancermentioning
confidence: 99%
“…Another article also reported that wild-type p53 can bind to G-quadruplexes on MYC promoter to repress MYC expression [ 80 ]. Both wild-type and non-gain-of-function p53 mutants can activate lincRNA-p21 through binding to G-quadruplexes on lincRNA-p21 promoter [ 81 ], and lincRNA-p21 can repress STAT3 [ 82 ]. STAT3 can bind to the HSP70 promoter to active HSP70 expression [ 83 , 84 ].…”
Section: Factors Influencing P53 Mutant Gain Of Functionmentioning
confidence: 99%